2015
DOI: 10.1371/journal.pone.0145693
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course of Chlamydia trachomatis Bacterial Load in the Time Interval between Screening and Treatment in Anogenital Samples

Abstract: IntroductionAlthough Chlamydia trachomatis (CT) is the most common bacterial sexually transmitted infection worldwide, little is known about the natural course of the bacterial load during infection. We investigated the natural course of the bacterial load in the interval between screening and returning for treatment in genital and anorectal CT-infections.Materials & MethodsCT-positive patients, visiting our STI-clinic in the Netherlands from June 2011–January 2014, provided a second urogenital and/or anorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…In line with our results, natural clearance of CT DNA and/or RNA during the period between CT detection and treatment has previously been assessed and varied between 9–44% in urogenital samples [25, 26]. Furthermore, in a recent study by our research group we have reported that CT load during the period between CT detection and treatment decreased more than 90% in one out of five of vaginal swab samples [27]. …”
Section: Discussionsupporting
confidence: 89%
“…In line with our results, natural clearance of CT DNA and/or RNA during the period between CT detection and treatment has previously been assessed and varied between 9–44% in urogenital samples [25, 26]. Furthermore, in a recent study by our research group we have reported that CT load during the period between CT detection and treatment decreased more than 90% in one out of five of vaginal swab samples [27]. …”
Section: Discussionsupporting
confidence: 89%
“…A general limitation of CT load-based studies is that the variability of low and high CT loads, and therefore high and low Cq values, in populations and individuals seems dependent of different factors, including time of diagnosis since infection; this hampers interpretation. For example, our study group assessed the natural course of the CT load during infection between screening and treatment and observed a decrease in CT load in 17–41% of the STI clinic patients dependent on sample type [26]. A limitation of the current study was that we were unable to validate Cq values for (1) other populations than the STI clinic population and (2) for urine samples of men.…”
Section: Discussionmentioning
confidence: 96%
“…We tested the use of the Cq value as a proxy for CT load by comparing derived Cq values with quantified CT load values from our previous studies [11, 25, 26]. CT load values were available from a subset of the STI clinic population, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst diagnosis for many infectious diseases requires the detection of pathogenic DNA/RNA concentrations as low as 10 copies/mL, there are some diseases where infectious pathogens are present at much higher concentrations and are within the scope of what the Subzyme PMB method can detect [20,21]. For example, one study reports that 85.8% (254/296) of positive C. trachomatis specimens had a bacterial load above the quantification limit of the qPCR (1 × 10 6 copies/mL) [22]. Furthermore, pathogens that are known to cause urinary tract infections (UTIs) such as Escherichia coli, Klebsiella spp., Pseudomonas aeuroginosa and Staphylococcus saprophyticus are typically present in urine samples at concentrations ranging between 1 pM-1 nM, which are also within the current detectable concentration range of the Subzyme feedback method [21,23].…”
Section: Subzyme Feedback Cascade Using Pmbsmentioning
confidence: 99%